Safety of deferring review after uneventful cataract surgery until 2 weeks postoperatively. Issue 12 (December 2015) - Kessel, Line; Andresen, Jens; Erngaard, Ditte; Flesner, Per; Tendal, Britta; Hjortdal, Jesper
Abstract : N/A: We conducted a systematic review and metaanalysis to provide evidence‐based recommendations on the value of early postoperative review. We identified 3 randomized controlled trials (RCTs) that compared patients seen on the first postoperative day with those reviewed at 2 weeks; the 3 studies comprised 886 patients. The risk for postoperative complications was lower when review was deferred 2 weeks because of early transient pressure spikes. There was no difference in the number of unscheduled visits during the first 2 weeks postoperatively or the visual acuity at follow‐up. No safety was gained by reviewing patients on the first postoperative day, and we recommend that routine early postoperative control can be omitted in nonglaucomatous patients after uneventful surgery if symptomatic patients are seen by an ophthalmologist as needed. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.